GROWTH AND YIELD RESPONSE OF CHICKPEA TO CO-INOCULATION WITH MESORHIZOBIUM CICERI AND BACILLUS MEGATERIUM - M. A. Qureshi; M. A. Shakir; M. Naveed; M. J. Ahmad (Journal of Animal and Plant Sciences, 2009)
Among rhizosphere microflora, a subset is beneficial to plant growth through N2-fixation, P-solubilization and hormone production. A pot experiment was conducted to evaluate the effect of co-inoculation with Mesorhizobium ciceri and Bacillus megaterium on growth and yield of chickpea at different fertilizer levels (0-15, 15-30, 30-60 kg NP ha-1). Results revealed that Mesorhizobium and Bacillus significantly increased the yield of chickpea yield as compared to control. However, co-inoculation of M. ciceri and B. megaterium further enhanced pod yield in comparison with uninoculated controls. Co-inoculation produced 25.77 g pot-1 pod and 29.07 g pot-1 straw yield whereas rhizobial inoculation produced 24.77 g pot-1 pod yield and 28.57 g pot-1 straw yield at full fertilizer level. Similarly, co-inoculation produced higher root fresh weight (181.4 g), root length (58.4 cm) and number of nodules per pot (61) as compared to uninoculated (94.7 g, 52.1 cm and 14) control. Mesorhizobium and Bacillus inoculation also increased the NP contents in chickpea straw and grain but this effect was more with co-inoculation. Inoculation significantly enhanced post harvest soil N and P. Results suggested that co-inoculation (M. ciceri and B. megaterium) could be an effective approach at recommended NP fertilizer than single strain inoculation; however, more extensive field studies are needed in different ecologies to reinforce this approach.
Keywords: Co-inoculation; Mesorhizobium; Bacillus; nodulation; yield; chickpea